Selection of cell-type specific antibodies on tissue-sections using phage display - Larsen, Simon Asbjørn (J Cell Mol Med, 2015)
With the advent of modern technologies enabling single cell analysis, it has become clear that small sub-populations of cells or even single cells can drive the phenotypic appearance of tissue, both diseased and normal. Nucleic acid based technologies allowing single cell analysis has been faster to mature, while technologies aimed at analysing the proteome at a single cell level is still lacking behind, especially technologies which allow single cell analysis in tissue. Introducing methods, that allows such analysis, will pave the way for discovering new biomarkers with more clinical relevance, as these may be unique for microenvironments only present in tissue and will avoid artifacts introduced by in vitro studies. Here, we introduce a technology enabling biomarker identification on small sub-populations of cells within a tissue section. Phage antibody libraries are applied to the tissue sections, followed by washing to remove non-bound phage particles. To eliminate phage antibodies binding to antigens ubiquitously expressed and retrieve phage antibodies binding specifically to antigens expressed by the sub-population of cells, the area of interest is protected by a ‘shadow stick’. The phage antibodies on the remaining areas on the slide are exposed to UV light, which introduces cross-links in the phage genome, thus rendering them non-replicable. In this work we applied the technology, guided by CD31 expressing endothelial cells, to isolate recombinant antibodies specifically binding biomarkers expressed either by the cell or in the microenvironment surrounding the endothelial cell.